Akranes And Borgarfjordur District Heating System - Ragnarsson, A. (Geo-Heat Center, Oregon Institiute of Technology, Klamath Falls, OR (USA), 1998)
In Iceland, there are about 30 geothermal district heating systems in operation in towns and villages. In most cases, they serve practically the total population of the respective communities, and totally about 83% of the house heating market in the country. All of them are community-owned, and they distribute and sell hot water on the basis of a monopoly. In addition to this, there are about 25 small privately-owned systems, each serving 50 people or more, mainly in rural areas, and a great number of smaller systems serving individual farms. Thus, the total share of geothermal heating in the country is about 85%. Reykjavik Municipal Heating is by far the largest of the district heating systems serving about 155,000 people, or more than half of the population of the country. The total installed capacity of all the geothermal district heating systems in Iceland is about 1,400 MW.